THE GREEN ECONOMY: PATHWAYS TO SUSTAINABLE DEVELOPMENT - Abdullaeva Barchinoy Yuldashevna (European Science Publishing, 2024)
The green economy represents a paradigm shift towards sustainability, prioritizing environmental health alongside economic growth. This article explores the foundations and evolution of the green economy, highlighting critical sectors such as renewable energy and sustainable agriculture. Through an analysis of policies and strategies, the paper identifies challenges and offers solutions to overcome barriers. Case studies illustrate successful transitions, providing a roadmap for future efforts. The green economy is crucial for mitigating climate change and fostering global sustainability.
Keywords: Green economy, sustainable development, renewable energy, circular economy, climate change, environmental policy, eco-friendly practices.